The relationship between cardiopulmonary exercise test variables, the systemic inflammatory response, and complications following surgery for colorectal cancer - Stephen T. McSorley; Campbell S. D. Roxburgh; Paul G. Horgan; Donald C. McMillan (Perioperative Medicine, 2018)
Abstract Background Both preoperative cardiopulmonary exercise test (CPET)-derived measures of fitness and postoperative C-reactive protein (CRP) concentrations are associated with complications following surgery for colorectal cancer. The aim of the present pilot study was to examine the relationship between CPET and postoperative CRP concentrations in this patient group. Methods Patients who had undergone CPET prior to elective surgery for histologically confirmed colorectal cancer in a single centre between September 2008 and April 2017 were included. Preoperative VO2 at the anaerobic threshold (AT) and peak exercise were recorded, along with preoperative modified Glasgow Prognostic Score (mGPS) and CRP on each postoperative day. Results Thirty-eight patients were included. The majority were male (30, 79%), over 65 years old (30, 79%), with colonic cancer (23, 61%) and node-negative disease (24, 63%). Fourteen patients (37%) had open surgery and 24 (63%) had a laparoscopic resection. A progressive reduction in VO2 at peak exercise was significantly associated with both increasing American Society of Anesthesiology (ASA) grade (median, ml/kg/min: ASA 1 = 22, ASA 2 = 19, ASA 3 = 15, ASA 4 = 12, p = 0.014) and increasing mGPS (median, ml/kg/min: mGPS 0 = 18, mGPS 1 = 16, mGPS 2 = 14, p = 0.039) There was no significant association between either VO2 at the AT or peak exercise and postoperative CRP. Conclusions The present pilot study reports a possible association between preoperative CPET-derived measures of exercise tolerance, and the preoperative systemic inflammatory response, but not postoperative CRP in patients undergoing surgery for colorectal cancer.